2014
DOI: 10.1097/ccm.0b013e3182a667f0
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Catheter Placement by Advanced Practice Nurses Demonstrates Low Procedural Complication and Infection Rates—A Report From 13 Years of Service*

Abstract: This report has demonstrated low complication rates for a hospital-wide service delivered by advance practice nurses. The results suggest that a centrally based service with specifically trained operators can be beneficial by potentially improving patient safety and promoting organizational efficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 31 publications
1
59
0
3
Order By: Relevance
“…CVAD insertion complications occur in 0.4–4.5% of procedures, in comparison to post-insertion complications, which can occur in up to 25% of the device life [5, 204206]. CVADs are designed for prolonged use compared to peripheral intravenous catheters, and more evidence for post-insertion care is needed to avoid unnecessary complications and the need for catheter replacement.…”
Section: Discussionmentioning
confidence: 99%
“…CVAD insertion complications occur in 0.4–4.5% of procedures, in comparison to post-insertion complications, which can occur in up to 25% of the device life [5, 204206]. CVADs are designed for prolonged use compared to peripheral intravenous catheters, and more evidence for post-insertion care is needed to avoid unnecessary complications and the need for catheter replacement.…”
Section: Discussionmentioning
confidence: 99%
“…A well-trained nursing team, as well as comprehensive and detailed education, would ensure PICC being used with slight complication [17]; however, because of the little evidence regarding radiation impact on PICC, the Michigan Appropriateness Guide for Intravenous Catheters (MAGIC) suggested that interval placement of PICCs with each chemotherapy treatment may be the most appropriate strategy [14]. Such strategy needs repeated intravenous punctures that increase a patient’s cost and pain and may result in higher complication rates [18]. …”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] The secondary outcomes were CVAD complications after successful CVAD insertion. These were as follows: (1) CVAD-associated BSI: minimum definition of a laboratory-confirmed BSI that is not secondary to an infection at another body site, with a CVAD in place for .2 days 20 ; (2) CVAD-associated thrombosis: development of thrombosed vessel (partial or complete) at the CVAD site diagnosed via ultrasound 30 ; (3) occlusion or blockage: as defined by study investigators, including partial and full blockage of the CVAD lumen or lumens, irrespective of occlusion treatment 30 ; (4) dislodgement or migration: as defined by study investigators, including partial, complete, and accidental removal resulting in the CVAD tip no longer being placed in the inferior or superior vena cava 5 ; (5) breakage or rupture: as defined by study investigators, including a visible split in CVAD material diagnosed by leakage or radiographic evidence of extravasation from a portion of the CVAD into tissue 13 ; and (6) local infection and phlebitis: as defined by the study investigators, including exit, entrance, and tunnel infections and phlebitis. 5 …”
Section: Outcome Measuresmentioning
confidence: 99%
“…10 Their insertion can result in complications including pneumothorax, arterial puncture, hemorrhage, and cardiac rhythm dysfunction, 11 with overall CVAD insertion-related complications reported in 7% to 18% of CVAD insertions. 12,13 The more CVADs a child has had, the more complex the procedure becomes, as CVAD failures can result in venous damage and insufficiency. 12 Even after successful CVAD insertion, many mechanisms may result in CVAD failure or complications, many of which are considered preventable.…”
mentioning
confidence: 99%